Distribution of ga vacancies in Zn diffused GaAs - Zahari Mohamed Darus,; Iftekhar Ahmed, (1992)
A detailed discussion on the distribution and the characteristics of vacancy profiles in Zn diffused GaAs is presented in this paper. Vacancies are consumed during the diffusion process, creating short-fall in the equilibrium vacancy concentration. The crystal tries to recover this short-fall by vacancy diffusion and vacancy generation process. In course of time, the depth in the vacancy short-fall decreases, but this short-fall propagates deeper into the crystal